Performance Evaluation of Vannamei Shrimp (Litopenaeus vannamei) Culture in Round Ponds (Millennial Shrimp Farm) under Applied Management Practices at BPBAP Ujung Batee - Nanda Fitriah; Kurnia; Humeira; Ali Afwanudin (Journal Informatic, Education and Management (JIEM), 2026)
This study evaluated the growth and production performance of vannamei shrimp (Litopenaeus vannamei) cultured in round ponds using the Millennial Shrimp Farm (MSF) system under applied management practices at BPBAP Ujung Batee up to 60 days of culture (DOC 60). Performance parameters included average body weight (ABW), average daily growth (ADG), survival rate (SR), feed conversion ratio (FCR), biomass, and water quality, analyzed descriptively and presented as mean ± standard deviation. At DOC 60, shrimp reached an ABW of 5.25 ± 2.86 g·ind⁻¹ and an ADG of 0.21 ± 0.06 g·ind⁻¹·day⁻¹, with survival rates ranging from 84 to 89% and an FCR of approximately 1.4. Ammonia concentration ranged from 0.02 to 1.65 mg·L⁻¹ and showed a strong negative relationship with survival rate (r = −0.94). These results indicate that shrimp performance during the mid-culture phase was maintained within acceptable ranges, with ammonia control being a key factor influencing survival.